Analisis Bahasa Ken dalam Reality Show Dairy Sarwendah - Indah Wahyuningsih; Meita Ardya Fahma; Muhammad Rais Almajid (ESTETIK : Jurnal Bahasa Indonesia, 2020)
This study aimed to describe Ken language in a reality show "Sarwendah Diary". In sociolinguistic studies, Ken language is included in the variety of languages as a form of various languages used by certain groups of people. This study used a descriptive qualitative research by describing the use of Ken language contained in a reality show. The documentation technique was used for data retrieval by listening, taking notes, and portraying from the realty show video "Sarwendah's Diary". Content analysis technique was used in this study to get the deep meaning of each Ken language used. In addition, the method of triangulation was also applied as to pursue the data validity. Based on the results of the analysis, Ken language was found in some videos entitled (1) Sarwendah Becomes a Scavenger in Medan, (2) the Disguise of Sarwendah and Betrand Peto in Makassar  Sarwendah diary, (3) Willingly Lendinga Cell Phone to a Scavenger, This Pecel Seller Gets a Fortune from Sarwendah, (4) Running Out of Costs Sarwendah is Assisted by a Vegetable seller. From the videos, we found several Ken languages that Sarwendah used in her disguise.